2019
DOI: 10.1073/pnas.1821218116
|View full text |Cite
|
Sign up to set email alerts
|

Combination anti–CTLA-4 plus anti–PD-1 checkpoint blockade utilizes cellular mechanisms partially distinct from monotherapies

Abstract: Immune checkpoint blockade therapy targets T cell-negative costimulatory molecules such as cytotoxic T lymphocyte antigen-4 (CTLA-4) and programmed cell death-1 (PD-1). Combination anti–CTLA-4 and anti–PD-1 blockade therapy has enhanced efficacy, but it remains unclear through what mechanisms such effects are mediated. A critical question is whether combination therapy targets and modulates the same T cell populations as monotherapies. Using a mass cytometry-based systems approach, we comprehensively profiled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
169
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(196 citation statements)
references
References 55 publications
12
169
0
4
Order By: Relevance
“…Anti-PD-1 monotherapy results in the expansion of exhausted CD8+ T cells, while dual therapy results in the expansion of activated terminally differentiated effector CD8+ T cells [106]. Anti-CTLA-4 monotherapy increases the expansion of Th1-like CD4+ T cells, while dual therapy further increases the frequency of this population [106,107]. These data confirm that combinational therapies benefit from unique mechanisms of action that cannot be inferred from monotherapies alone.…”
Section: Anti-ctla-4 and Anti-pd-1mentioning
confidence: 54%
See 1 more Smart Citation
“…Anti-PD-1 monotherapy results in the expansion of exhausted CD8+ T cells, while dual therapy results in the expansion of activated terminally differentiated effector CD8+ T cells [106]. Anti-CTLA-4 monotherapy increases the expansion of Th1-like CD4+ T cells, while dual therapy further increases the frequency of this population [106,107]. These data confirm that combinational therapies benefit from unique mechanisms of action that cannot be inferred from monotherapies alone.…”
Section: Anti-ctla-4 and Anti-pd-1mentioning
confidence: 54%
“…Though both therapies target immune checkpoints that attenuate T-cell activation, they do so through distinct mechanisms that differentially affect specific T-cell populations [105]. Anti-PD-1 monotherapy results in the expansion of exhausted CD8+ T cells, while dual therapy results in the expansion of activated terminally differentiated effector CD8+ T cells [106]. Anti-CTLA-4 monotherapy increases the expansion of Th1-like CD4+ T cells, while dual therapy further increases the frequency of this population [106,107].…”
Section: Anti-ctla-4 and Anti-pd-1mentioning
confidence: 99%
“…CD279 antagonizes the TCR signaling pathway by a different mechanism compared to that of CD152 despite their synergy in the negative regulation of T cell activation [26]. Apart from differential expression pattern between CD279 and CD152 and their ligands in various cell subpopulations and tissues, they differ in their downstream signaling pathways with respect to inhibiting the upregulation of glucose metabolism and Akt phosphorylation mediated by CD3/CD28.…”
Section: Discussionmentioning
confidence: 99%
“…While it has been reported that anti-PD-1 and anti-CTLA-4 combination therapy increases the incidence and severity of adverse effects, these were observed to be linked to the beneficial anti-tumor immune response; an inherently anti-"self" immune response capable of targeting non-tumor "self" targets throughout the body [50]. Management of immune-related adverse events (irAEs) are often handled with corticosteroids or discontinuation of treatment and are often considered by clinicians to be manageable with proper dosing.…”
Section: Discussionmentioning
confidence: 99%